The prostacyclin analogue iloprost increases circulating endothelial progenitor cells in patients with critical limb ischemia - Di Stefano, Rossella; Barsotti, Maria Chiara; Melillo, Elio; Iorio, Mariacarla; Santoni, Tatiana; Armani, Chiara; Dell’Omodarme, Matteo; Ristori, Chiara; De Caterina, Raffaele; Balbarini, Alberto (Thrombosis and Haemostasis, 2008)
Patients with critical limb ischemia (CLI) have low levels of endothelial progenitor cells (EPC). Iloprost has been demonstrated to stimulate vascular endothelial growth factor (VEGF) and promote angiogenesis. We investigated the effects of iloprost on EPC levels in vivo in CLI patients. Twenty-three patients with stage III and IV CLI were treated with iloprost for four weeks, improving clinical and instrumental parameters. Mononuclear cells isolated from peripheral blood were cultured to obtain “early” EPC, evaluated counting adherent cells with double positivity for acetylated low-density lipoprotein uptake and Ulex Europaeus lectin at flow cytometry. These cells also co-expressed the monocyte markers CD14 and CD45.Iloprost increased EPC number in the whole patient population: pre-treatment median: 13,812/ml; range: 1,263–83,648/ml; post-treatment median: 23,739/ml; range: 3,385–99,251/ml; p=0.035, irrespective of age, sex, disease stage or atherosclerosis risk factors. In conclusion, iloprost increases EPC number in peripheral blood in vivo. Such an effect may have therapeutic relevance.
Keywords: Endothelial progenitor cells; stem cells; angiogenesis; critical limb ischemia; peripheral arterial disease